Exploration of a low-cost digital beamforming radar - Wang, Xiaohui (2019)
Walabot is a small-sized digital beamforming radar with multi-function. That is the reason why it is so popular in DIYers. In this project, I will analyze the raw signal data which is extracted from Walabot, the purpose is to realize more about it and the working principle of radar itself. In the process of exploration, study how to use the new programming software Python and use its relevant toolkits to discover the usable data.